Несколько утверждений для выпуклых функций - Степанец, А.И. (Український математичний журнал, 1999)
Наведено розбиття множини опуклих донизу функцій Ψ(∙), що зникають на нескінченності, на підмпожини за поведінкою їх спеціальних характеристик η(Ψ;∙) та μ(Ψ;∙). Вивчаються геометричні та аналітичні властивості елементів цих підмножин, які потрібні при розгляді задач теорії наближень для класів згорток. For the setM of convex-downward functions Ψ (•) vanishing at infinity, we present its decomposition into subsets with respect to the behavior of special characteristics η (Ψ;•) and μ(Ψ;•) of these functions. We study geometric and analytic properties of the elements of the subsets obtained, which are necessary for the investigation of problems of the theory of approximation for classes of convolutions.